Tracking Social Capital Outcomes and Sustainability of Local Policies in Natural Resources Management1 - Sanginga, Pascal C.; Kamugisha, Rick; Abenakyo, Annet; Muzira, Robert (International Centre for Tropical Agriculture (CIAT), 2006)
It is now well recognized that social capital is an important asset upon which poor people draw in pursuit of their livelihood objectives. Social capital has the characteristic of a public good; with the implication that it can be created and strengthened. Five years ago, we initiated a participatory learning and action research project on ‘Strengthening social capital for improving policies and decision making in NRM’ in the southwestern highlands of Uganda. The project aimed at stimulating and facilitating participatory social learning processes to increase the skills and knowledge of communities, their leadership capacity, and their motivations to act and create conditions for the formulation and implementation of appropriate community byelaws and local policies that can lead to better management of natural resources. Among other results, four pilot communities formulated a number of byelaws for improving NRM based on participatory visioning and community action plans, and established social capital mechanisms for monitoring their implementation and enforcement. One year after project completion, we initiated a study to find answers to important questions such as: What has happened since project completion? Does strengthened social capital translate into improved participation in policy formulation and implementation? Does it translate into better management of natural resources, or accelerated adoption of improved NRM technologies? What are the conditions for sustainability of participatory policy processes? Who benefits and who loses, and in what ways? The purpose of this study was to track the outcomes, potential impacts and conditions for sustainability of byelaws and social capital processes for policy action. The study was conducted in five communities one year after the end of the action research, using a combination of participatory tools, household surveys and participatory land degradation assessment. More specifically we used the After Action Review (AAR) and “Peer Assist ” techniques. These are interactive group-based participatory techniques to facilitate a critical reflection of the performance, the outcomes, uptake and conditions for sustainability of village policy task forces; community action plans and selected byelaws. Results reveal that there have been considerable effects on three key components of rural livelihoods: social capital, human capital, and natural capital. There is evidence of increasing trust, cooperation, collective action, awareness and compliance to collective norms and rules or byelaws, as well as participation in community meetings and collective action initiatives for the implementation of the erosion control and tree planting byelaws. The number of collective action events for byelaw implementation varied between three and seven within a year after project completion. There is also evidence of increased women participation in community events and decision-making, assertiveness, leadership, confidence and sense of self worth, which are important indicators of empowerment of women in a patriarchal society. The physical outcomes of the two byelaws, and the performance of the PTF were measured in terms of the extent of land degradation, number of trees planted, number of trenches constructed and farmers’ perceptions of NRM improvement. While there is evidence of attempts to control soil erosion through the implementation of byelaws on making trenches, it is still too early to make a robust assessment of the impacts of strengthened social capital on sustainable natural resources management. The effectiveness of byelaws was often constrained by lack of appropriate technologies, political interference and limited support from policy makers. Despite serious challenges faced by the different community policy initiatives, there is evidence of sustainability of such initiatives in certain communities, while their continued functioning and effectiveness in other communities remain a key challenge. All the five policy task forces continued to function, one year after project intervention, with different levels of consistency. These policy task forces have been very effective in creating awareness about the byelaws, in mobilizing people to participate in collective actions, monitoring the compliance of the byelaws, providing feedback to the community, and linking the community to the District and NGO partners. The more performing PTFs are embedded in decentralized local government structures and farmers groups at the village level, with the majority of its members doubling also as local councilors and members of the executive committees of agricultural-related groups. They have managed to create community and political alignment and support of the byelaws through leaderships and shared visions of desired future conditions. The less performing were seen as parallel structures to the local council, and were not sufficiently integrated in existing farmers groups; creating some levels of e conflicts and confusion. The most important reason for expecting sustainability and potential impacts is that the PTFs continued to function, farmers are enthusiastic and continue to participate in byelaws implementation, and are eager to initiate new activities and link with other rural service providers. New villages have also initiated similar processes. Some PTF members have been contracted by the district to provide facilitation services on institutional development to other farmer groups in neighbouring communities. Although there are strong indications and willingness of sustainability, tracking changes and isolating outcomes of such processes over time, and their influencing factors five years after an intervention